Research of General Deduction Optimization on PEMFC Manufacturing with Fuzzy Linguistic Analysis. (15th December 2013) - Lan, Tian-Syung; Huang, Han-Chen; Hou, Cheng-I
Abstract : In control questions, multiquality parameters are the most suitable, as they are everlasting in highly complex misalignment relations; the relationship between the parameter and quality of mutual influence is complex, and often massive redundant operations must be achievable by the test installation. Because the most suitable multiquality parameter is difficult to achieve, this study designates the proton exchange membrane fuel cell as the topic, takes the inlet temperature, inlet pressure, and incoming flow speed as the controlling elements, uses conformity fuzzy meaning analysis and the ideal solution similar order by chance law (TOPSIS), and discusses the parameters to control the influences of the quality goal. As outlet temperature, outlet pressure, pressure drop do not operate after the experiment, this study uses the meaning deduction method and develops a set of the most suitable control mechanisms. The research results show that this study develops a quality decision scheme for a set of meanings by using the misalignment and a high order complexity question. It also penetrates the meaning method, which guarantees that the quality and experimental efficiency may elevate the competitive power of science and technological undertakings development, effectively economize costs, and provide a set of economies and perspectives. The multiqualities are the most suitable control plan which meets the demands of practice.